Scholastic Jesuit Theatre – a Part of Political Theatre in Great Duchy of Lithuania - Ulčinaitė, Eugenija (Literatūra, 2015)
At the beginning scholastic Jesuit theatre was considered to be a part of didactic teaching programme. During their performances students were trained to associate with spectators, develop their memory, articulation, review the knowledge of the Latin language, meditate upon religious, moral values. New academic years used to begin and end with students’ performances, they supplemented various state and religious celebrations, gave honour to outstanding heroes of past and present. Eventually, however, scholastic theatre overgrew these didactic aims: from academic lecture-halls they spread into the streets and squares of the town, became inseparable part of the town life, helped to form esthetic taste of spectators, impressively expressed the baroque spirit. The article analysis comedies, recitations and paratheatrical plays performed by the students of old Vilnius university show in political and social events by using different theatre forms. The biggest part of the analysis is devoted to the drama “About peace” written by the university professor Kasper Pentkovski (Kasper Pætkowski, 1554–1612). It was written and performed in 1582 in Vilnius when King of Poland and Great Duke of Lithuania Steponas Batoras returned after winning the war and signing the peace treaty with Moscow tzar Ivan the Terrible. The drama describes the hardships caused by the war, the sufferings, the loss, religious disunity, and belief that the treaty signed by Steponas Batoras will bring harmony, peace and help to strengthen catholic faith. Thus, Jesuit scholastic theatre very sensitively reacted both to local and European political changes, it might be called ‘engagé’ theatre trying to conciliate didactic and political goals.